2015
DOI: 10.1007/s00261-015-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of and agreement between MR imaging and spectroscopic estimation of hepatic proton density fat fraction in children with known or suspected nonalcoholic fatty liver disease

Abstract: Purpose To assess feasibility of and agreement between magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) for estimating hepatic proton density fat fraction (PDFF) in children with known or suspected nonalcoholic fatty liver disease (NAFLD). Material and Methods Children were included in this study from two previous research studies in each of which three MRI and three MRS acquisitions were obtained. Sequence acceptability, and MRI- and MRS-estimated PDFF were evaluated. Agreement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
4
13
0
2
Order By: Relevance
“…However, some studies provided a better correlation. It should be noted that the range of values was larger in these studies (0–40% than in the present study (0–12%). Especially, it is challenging to accurately estimate very low fat content in liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies provided a better correlation. It should be noted that the range of values was larger in these studies (0–40% than in the present study (0–12%). Especially, it is challenging to accurately estimate very low fat content in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the feasibility of assessing the composition of fat based on multiple gradient echo imaging also named CSE‐MRI. Studies focusing on liver diseases have extensively compared the MRS and MRI methods for the quantification of the PDFF …”
mentioning
confidence: 99%
“…Despite the growing clinical and research interest in these techniques, a standardized approach for ROI-based measurements has not been established. As a result, recent studies conducted at different sites have used a wide range of ROI sizes (from 0.785 cm 2 to the whole liver), locations (left and right lobes; anterior, posterior, and lateral segments; Couinaud segments; whole liver), and number (one to nine ROIs) for measurements of liver PDFF and R2* [6, 8, 16, 2125]. This lack of standardization introduces an additional element of variability across sites and studies, impacting the widespread dissemination of these techniques as reproducible and repeatable quantitative imaging biomarkers.…”
mentioning
confidence: 99%
“…Um exame que tem ganhado grande destaque na literatura nos últimos anos é a RNM por espectroscopia (MRS), que apesar de ter grande acurácia, é um exame demorado e de difícil execução, por este motivo, no presente estudo elegemos a RM por imagem, pois tem risco mínimo, é não invasiva, mais rápida e mais fácil de realizar do que a MRS. Os resultados da RNM são mais precisos do que o ultrassom, não utiliza radiação ionizante, e fornece cobertura espacial de todo o fígado. Apesar da literatura referir que os exames de RNM em crianças pode ser um desafio por causa da apnéia, limitando a capacidade ou tolerância deste exame, podendo resultar em artefato de movimento e/ou exigindo modificação nos parâmetros da RNM para reduzir o tempo de apnéia (ACHMAD et al, 2015), não encontramos no presente trabalho tal dificuldade. Verificamos que ressonância nuclear magnética por imagem é um exame factível de ser executado em crianças e adolescentes, podendo representar uma ferramenta diagnóstica eficaz e não invasiva de esteatose hepática nesta faixa etária.…”
Section: Discussionunclassified
“…É um método não-invasivo, considerado exato e preciso, no entanto é demorado, tecnicamente difícil, restrito em cobertura espacial e, atualmente, só está disponível em alguns centros (ACHMAD et al, 2015).…”
Section: Camilo 2004)unclassified